Phonons of electronic crystals in two‐dimensional semiconductor moiré patterns - Hongyi Yu; Jiyong Zhou (Natural Sciences, 2023)
Abstract We theoretically studied the phonon properties of the triangular‐, stripe‐, and honeycomb‐type electronic crystals recently found in two‐dimensional semiconductor moiré patterns. By analyzing the phonon dispersions, we found the interaction induced lattice deformation in the zigzag‐stripe crystal results in a much higher dynamical stability than in the linear‐stripe crystal. Moreover, chiral phonons with finite magnetizations and large Berry curvatures can emerge in triangular and honeycomb crystals under time‐reversal or inversion symmetry breaking. The small effective mass of the electrons allows the selective and efficient generation of chiral phonons from the optical activity of zone‐center phonons combined with the anharmonicity, facilitating the realization of the phonon Hall effect. These findings point to an exciting new platform for exploring chiral phonons and related topological phononic devices. Key points The phonons of the electronic crystals in semiconductor moiré systems are systematically analyzed, which can lead to the infrared absorption, Raman scattering, and Hall effect of chiral phonons. The small effective mass of the electrons as compared to their ionic counterparts facilitates tuning the chiral phonons through external fields, which may stimulate further studies about elementary excitations of the intriguing correlated insulators in moiré systems. Our study connects the two active research fields of strongly correlated physics and chiral phonons.